Model for electrodes' filaments of hot cathode fluorescent lamps, during preheating with constant rms current - Wakabayashi, Fabio Toshiaki; Ferreira, Castellane Silva; Gomes de Brito, Moacyr Aureliano; Canesin, Carlos Alberto (Institute of Electrical and Electronics Engineers (IEEE), 2007)
This paper presents a new model for the representation of electrodes' filaments of hot-cathode fluorescent lamps, during preheating processes based on the injection of currents with constant root mean square (rms) values. The main improvement obtained with this model is the prediction of the R-h/R-c ratio during the preheating process, as a function of the preheating time and of the rms current injected in the electrodes. Using the proposed model, it is possible to obtain an estimate of the time interval and the current that should be provided by the electronic ballast, in order to ensure a suitable preheating process. is estimate of time and current can be used as input data in the design of electronic ballasts with programmed lamp start, permitting the prediction of the R-h/R-c ratio during the initial steps of the design (theoretical analysis and digital simulation). Therefore, the use of the proposed model permits to reduce the necessity of several empirical adjustments in the prototype, in order to set the operation of electronic ballasts during the preheating process. This fact reduces time and costs associated to the global design procedure of electronic ballasts.
Keywords: electrodes' filaments; electronic ballasts; fluorescent lamp model; preheating process